2013
DOI: 10.18632/oncotarget.1246
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer tumorigenicity and drug resistance are maintained through ALDHhiCD44hi tumor initiating cells

Abstract: Limited improvement in long term survival of lung cancer patients has been achieved by conventional chemotherapy or targeted therapy. To explore the potentials of tumor initiating cells (TIC)-directed therapy, it is essential to identify the cell targets and understand their maintenance mechanisms. We have analyzed the performance of ALDH/CD44 co-expression as TIC markers and treatment targets of lung cancer using well-validated in vitro and in vivo analyses in multiple established and patient-derived lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 40 publications
3
54
1
2
Order By: Relevance
“…This is consistent with studies indicating that ALDH activity or expression of one or more ALDH protein correlate with tumor aggressiveness, treatment resistance, metastasis, and poor patient prognosis (6,25,44). ALDH has been proposed as a prognostic marker for many cancers including lung (45), breast (46), ovarian (47), pancreatic (24), and colon (48). There are many excellent recent reviews of ALDHs in cancer and CSCs (6,(49)(50)(51)(52) and these topics will not be discussed in detail here.…”
Section: Figuresupporting
confidence: 81%
“…This is consistent with studies indicating that ALDH activity or expression of one or more ALDH protein correlate with tumor aggressiveness, treatment resistance, metastasis, and poor patient prognosis (6,25,44). ALDH has been proposed as a prognostic marker for many cancers including lung (45), breast (46), ovarian (47), pancreatic (24), and colon (48). There are many excellent recent reviews of ALDHs in cancer and CSCs (6,(49)(50)(51)(52) and these topics will not be discussed in detail here.…”
Section: Figuresupporting
confidence: 81%
“…CD44, which localizes to the cell membrane, is reportedly involved in cell migration in various cancer types [44]. Recent studies also showed that tumor initiating cells with high CD44 expression maintained lung cancer tumorigenicity and drug resistance [45]. Another metastasis-related gene induced by miR-182 knockdown, ADAM9, cleaves membrane proteins such as E-cadherin [46].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs have the ability to self-renewal and can produce differentiated progeny through their pluripotency (69). It has been demonstrated that these CSCs in lung cancer resist to chemotherapeutic agents and have high tumorigenic potential (12,70). Also, the lung CSCs were shown to have augmented ability to move to other tissues (8,12,71).…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Several CSC makers have been used to identify the CSC population in lung cancer, including cellular expression of CD44, CD133 and CD166 (67)(68)(69)(70)(71). Also aldehyde dehydrogenase (ALDH) activity and expression have been shown to indicate stemness in lung cancer (67)(68)(69)(70)(71).…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%